An Analysis of the Role and Perspectives of Female Landless Agricultural Labourers in the Guttal Block of the Haveri District (International Journal of Food and Nutritional Sciences, 2022)
This study describes the problems faced by landless women agriculture labourers, their occupational interests, and occupational diversity. In the study area, illiterate women workers are more and those with primary school education are more likely to be employed in agricultural work. There is a difference in earning agricultural wages (female and male) and this difference is based on hardship generally women workers earn an average wage of Rs 200 to 300.Landless women agricultural labourers are working at different distances from their place of residence, workplaces do not have fixed distances, currently more chemicals are used in farming activities, and there is information that some have side effects. In contrast, others have no side effects, and some women workers are subject to occupational limitations.